Complete Sequence of the Mitochondrial Genome of Spirometra ranarum: Comparison with S. erinaceieuropaei and S. decipiens - Jeon, Hyeong-Kyu; Park, Hansol; Lee, Dongmin; Choe, Seongjun; Kang, Yeseul; Bia, Mohammed Mebarek; Lee, Sang-Hwa; Eom, Keeseon S. (Korean journal of parasitology, 2019)
This study was undertaken to determine the complete mitochondrial DNA sequence and structure of the mitochondrial genome of Spirometra ranarum, and to compare it with those of S. erinaceieuropaei and S. decipiens. The aim of this study was to provide information of the species level taxonomy of Spirometra spp. using the mitochondrial genomes of 3 Spirometra tapeworms. The S. ranarum isolate originated from Myanmar. The mitochondrial genome sequence of S. ranarum was compared with that of S. erinaceieuropaei (GenBank no. KJ599680) and S. decipiens (GenBank no. KJ599679). The complete mtDNA sequence of S. ranarum comprised 13,644 bp. The S. ranarum mt genome contained 36 genes comprising 12 protein-coding genes, 22 tRNAs and 2 rRNAs. The mt genome lacked the atp8 gene, as found for other cestodes. All genes in the S. ranarum mitochondrial genome are transcribed in the same direction and arranged in the same relative position with respect to gene loci as found for S. erinaceieuropaei and S. decipiens mt genomes. The overall nucleotide sequence divergence of 12 protein-coding genes between S. ranarum and S. decipiens differed by 1.5%, and 100% sequence similarity was found in the cox2 and nad6 genes, while the DNA sequence divergence of the cox1, nad1, and nad4 genes of S. ranarum and S. decipiens was 2.2%, 2.1%, and 2.6%, respectively.